Factores Psicosociales que influyen en la aparición de conductas disruptivas en los adolescentes escolarizados según revisión documental (2020)
The general objective of this research was to analyze the psychosocial factors present in the disruptive behaviors of school adolescents according to a documentary review between 2010 and 2020, studies were identified that allowed access to the information that related the two categories proposed for this research, said search it was carried out through academic google, repositories and secondary sources such as indexed journals such as Redylac, scielo thus supporting bibliographic tracking for it. Among the results obtained, it was possible to show that both psychological and social factors are present in the appearance of disruptive behaviors, which are migrated to the classroom and evidenced through a series of challenging behaviors in relation to the classroom norm and group dynamics, the foregoing may be related to the social areas that make up the subject in community, where it encompasses its relationship with peers, and as the student in his construction of identity, responds to the environment where he develops, as a second instance is the family As the main nucleus of society, it provides the way to assume its role as an individual, where the young person learns to socialize and solve their problems.